# GMAT Prep From Platinum GMAT

### GMAT Prep Materials

### Announcement

Check out our latest blog post about The Best GMAT Books for Studying on Your Own.

### About Us

Platinum GMAT Prep provides the best GMAT preparation materials available anywhere, enabling individuals to master the GMAT and gain admission to any MBA program. We also provide hundreds of pages of free GMAT prep content, including practice questions, study guides, and test overviews.

Which of the following equations has at least one root in common with x

^{2}+ 11x + 10 = 0?Correct Answer:

**D**You only need to solve one equation

- First find the roots (or solutions) to the original equation.

*Option 1*: Factor the equation into (x + 10)(x + 1) = 0.

This means that the solutions to the equation (or roots) are x = -10 and -1.*Option 2*: Plug the equation into the quadratic formula with a=1, b=11, and c=10.

When worked out, this also reveals x = -10 or -1.

- It is possible to proceed by evaluating the answer choices in the same manner as step one then check which option has a root in common with the original equation. However, a faster approach is to simply plug the two solutions found in step one into each equation.
- Plug x= -10 and -1 into A:

(-10)^{2}- 11(-10) + 10 = 100+110+10 = 220.

(-1)^{2}- 11(-1) + 10 = 1+11+10 = 22.

Neither x = -10 nor x = -1 makes the equation equal to 0, so A can be ruled out. - Plug x = -10 and -1 into B:

(-10)^{2}+ 10(-10) - 11 = 100-100-11 = -11.

(-1)^{2}+ 10(-1) - 11 = 1-10-11 = -20.

Neither x = -10 nor x = -1 makes the equation equal to 0, so B can be ruled out. - Plug x = -10 and -1 into C:

(-10)^{2}+ 10(-10) + 11 = 100-100+11 = 11

(-1)^{2}+ 10(-1) + 11 = 1-10+11 = 2

Neither x = -10 nor x = -1 makes the equation equal to 0, so C can be ruled out. - Plug x = -10 and -1 into D:

2(-10)^{2}+ (-10) - 1 = 2(100)-10-1 = 189

2(-1)^{2}+ (-1) - 1 = 2(1)-1-1 = 0

x = -1 makes the equation equal to 0, so D is the answer, though it doesn't hurt to check the last answer to make sure. - Plug x = -10 and -1 into E:

2(-10)^{2}- (-10) - 1 = 2(100)+10-1 = 209

2(-1)^{2}- (-1) - 1 = 2(1)+1-1 = 2

Neither x = -10 nor x = -1 makes the equation equal to 0, so E can be ruled out. - After reviewing all the choices, only D has a common root with the original equation.